Α-Oxygenation of N-aryl/alkyl heterocyclic compounds via ruthenium photocatalysis. Issue 11 (10th September 2021) - Kumar, Inder; Thakur, Ankita; Manisha; Sharma, Upendra
Abstract : We herein report ruthenium(iii ) photocatalyzed oxidation of N -aryl tertiary amines to the corresponding amides. Abstract : We herein report ruthenium(iii ) photocatalyzed oxidation of N -aryl tertiary amines to the corresponding amides. More specifically, various N -aryl tetrahydroisoquinolines were converted to analogous N -aryl dihydroisoquinolinones under an oxygen atmosphere. Molecular oxygen is utilized for α-oxidation in the presence of benzylic proton abstracting base DBU to get oxidized products in good to excellent yields. Quenching experiments confirmed the radical pathway of the reaction through the formation of O2 ˙ − reactive oxygen species (ROS).